PENGARUH KUALITAS SISTEM, PEMANFAATAN SISTEM INFORMASI DAN MINAT PENGGUNA ACCURATE TERHADAP KINERJA INDIVIDU (Studi Kasus pada PT. Karunia Selaras Abadi) - Kumala, Rita Dewi; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test and to analyze some factors which influence the individual performance of the users of Accurate Accounting systems on PT. Karunia Selaras Abadi, i.e.: system quality, the utilization of information system, and the interest of the users of Accurate Accounting system. The method of this research is quantitative. The analysis technique has been done by using multiple linear analysis with SPSS 18. The result of the test shows that the influence of the variablesi.e. system quality, the utilization of information system, and the interest of the users to the individual performance of Accurate Accounting system is significant. This is indicatedby the acquisition of significance is 0.000 which is less than Î± = 5%. This condition shows that the fluctuation of individual performance on PT. Karunia Selaras Abadi has been determined by how well the company in conducting system quality, the utilization of information system, and the interest of the users. This condition is supportedby the acquisition of multiple correlation coefficients is 0.777 which shows the simultaneous correlation among these variables to the individual performance on PT. Karunia Selaras Abadi is firm. Keywords: System Quality, the Utilization of Information System, the Interest of the Users, individual Performance.